TiDE Model – Creating Plurilingual Digital Materials with Future Preschool Teachers - Sila, Anita; Klančar, Andreja (Revija za elementarno izobraževanje, 2024)
This article deals with developing plurilingual digital content with future preschool teachers. We present the TiDE (Teaching in Digital Education) model which promotes the development of digital didactic materials and relevant digital competences through active, experience-based, and interdisciplinary learning. A qualitative study was conducted focused on the process of designing new digital didactic materials for raising plurilingual awareness, i.e. stop-motion videos for preschool children. The data were obtained by analysing 16 stop-motion videos and feedback from 60 Slovenian first-year students of preschool education at the University of Primorska. The results suggest that new digital technologies can be very effective in developing engaging, effective, and learner-centered resources that promote students' plurilingual awareness and an open attitude towards linguistic and cultural diversity.